Just joking LOL! : 300 hilarious jokes about everything, including wacky tongue twisters, silly puns, funny photos, and much more! - Pattison, Rosie Gowsell (Washington, D.C. : National Geographic, 2017)
"Get ready to LOL! This collectible little book is packed with 300 silly kid-friendly jokes paired with photos of laughing animals and funny people. It's a hilarious party-starter or "quiet-time" entertainer, perfect to read alone or aloud with friends and family. It's also a great book to toss into a backpack to share at school or camp"--
OSLIS\Gale Nat Geo eBooks(2/2/23).
Description based on print version record.
Keywords: Wit and humor, Juvenile; Riddles, Juvenile; Wit and humor; Riddles; Jokes; Electronic books- OSLIS; Humor; Riddles; Children's nonfiction; Electronic books